PENGARUH CAPITAL ADEQUACY RATIO (CAR), BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSET (ROA) PADA PT. BANK DANAMON TBK PERIODE 2013-2022 - Lestiawati, Putri; Prestarika Lukito, Cristine (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Capital Adequancy Ratio (CAR), Operational Costs, Operational Income (BOPO) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) partially or simultaneously at PT. Bank Danamon Tbk Period 2013-2022. The method used is quantitative associative. The sample used is the financial report of PT Bank Danamon Tbk for the 2013-2022 period. This research uses descriptive statistical tests, classical assumption tests, hypothesis testing using the SPSS version 25 software program. The results of this research prove that partially the Capital Adequancy Ratio (CAR) variable does not have a significant effect on Return On Assets (ROA) with a value of tcount < ttable ( 0.098 < 2.4469) and a significant value of 0.925 > 0.05, then H01 is accepted and Ha1 is rejected. The variable Operational Costs Operational Income (BOPO) partially has no significant effect on Return On Assets (ROA) with a value of tcount < ttable (-0.585 < 2.4469) and a significant value of 0.580 > 0.05, so H02 is accepted and Ha2 is rejected. The variable Loan to Deposit Ratio (LDR) partially has a significant effect on Return On Assets (ROA) with a value of tcount > ttable (4.489 > 2.4469) and a significant value of 0.004 < 0.05, so H03 is rejected and Ha3 is accepted. Simultaneously the variables Capital Adequancy Ratio (CAR), Operational Costs Operational Income (BOPO), and Loan to Deposit Ratio (LDR) simultaneously have a significant effect on Return On Assets (ROA) with fcount > ftable (10.764 > 4.76) and value significant at 0.008 <0.05, with a coefficient of determination of 76.5% which is strong and the rest is explained by other factors.